Hubungan Tingkat Pendidikan Masyarakat Terhadap Pengetahuan dalam Penggunaan Antibiotik Oral di Apotek Kecamatan Koto Tangah Padang - Ringga Novelni (Jurnal Penelitian Farmasi Indonesia, 2020)
Antibiotics are drugs that are widely used for therapeutic treatment of infections, but now the purchase of antibiotics without a doctor's prescription at pharmacies has become a global problem, especially in developing countries. This study aims to determine the relationship of community education level to knowledge in the use of oral antibiotics in pharmacies in Koto Tangah District, Padang. The method used is descriptive correlative with cross-sectional approach. The population in this study were all people who visited the pharmacy in Koto Tangah District. The sampling technique uses non-random sampling technique that is purposive sampling of 100 respondents who have met the inclusion and exclusion criteria. Measuring instruments in this study used a questionnaire about knowledge in the use of oral antibiotics. Based on the results of the chi-square statistical test between the level of knowledge and the level of education obtained p = 0,000. This shows the p value is not greater than 0.05, and the relationship between the level of public education with knowledge in the use of Oral Antibiotics with the Spearman correlation test is 0.53, so it can be concluded that there is a relationship between the level of public knowledge and the level of public education in use of oral antibiotics.